Is there any difference between anterior and posterior approach for the spinal accessory to suprascapular nerve transfer? A systematic review and meta-analysis. (4th May 2023) - Makel, Michal; Sukop, Andrej; Kachlík, David; Waldauf, Petr; Whitley, Adam; Kaiser, Radek
ABSTRACT: Dual nerve transfer of the spinal accessory nerve to the suprascapular nerve (SAN-SSN) and the radial nerve to the axillary nerve is considered to be the most feasible method of restoration of shoulder abduction in brachial plexus injuries. Supraspinatus muscle plays an important role in the initiation of abduction and its functional restoration is crucial for shoulder movements. There are two possible approaches for the SAN-SSN transfer: the more conventional anterior approach and the posterior approach in the area of scapular spine, which allows more distal neurotization. Although the dual nerve transfer is a widely used method, it is unclear which approach for the SAN-SSN transfer results in better outcomes. We conducted a search of English literature from January 2001 to December 2021 using the PRISMA guidelines. Twelve studies with a total 142 patients met our inclusion criteria. Patients were divided into two groups depending on the approach used: Group A included patients who underwent the anterior approach, and Group B included patients who underwent the posterior approach. Abduction strength using the Medical Research Scale (MRC) and range of motion (ROM) were assessed. The average MRC grade was 3.57 ± 1.08 in Group A and 4.0 ± 0.65 (p = 0.65) in Group B. The average ROM was 114.6 ± 36.7 degrees in Group A and 103.4 ± 37.2 degrees in Group B (p = 0.247). In conclusion, we did not find statistically significant differences between SAN-SSN transfers performed from the anterior or posterior approach in patients undergoing dual neurotization technique for restoration of shoulder abduction.